A Factualistic Study of Phytomedicinal Activity of Curcuma longa (Haldi): Plant That Infuses Life - Mohd. Wasiullah; Piyush Yadav; Ankit Rai (International Journal of Antibiotics, 2025)
Curcuma longa, commonly known as turmeric, is a plant of remarkable medicinal significance that has been utilized for centuries in traditional medicine and has garnered considerable attention in modern scientific research. This review explores its extensive phytomedicinal potential, focusing on the plant's bioactive compounds, particularly curcumin, which is recognized as the primary agent responsible for its therapeutic properties. Turmeric contains an array of chemical constituents, including curcuminoids, volatile oils, and polysaccharides, contributing to its diverse pharmacological effects. These effects include anti-inflammatory, antioxidant, antimicrobial, anticancer, neuroprotective, and cardioprotective properties. Despite its therapeutic promise, the clinical application of curcumin faces significant challenges, primarily related to its poor bioavailability, rapid metabolism, and limited absorption. These issues necessitate innovative strategies, such as the use of curcumin analogs, nanoparticles, and combination therapies, to enhance its efficacy and stability. This review consolidates the current scientific evidence supporting turmeric's medicinal potential and underscores its clinical relevance. Furthermore, it highlights ongoing research aimed at overcoming the hurdles associated with curcumin's use in therapeutic contexts. By delving into its pharmacological activities and clinical implications, this article serves as a comprehensive resource for understanding Curcuma longa's potential as a versatile and effective natural therapeutic agent.
Keywords: Curcuma longa; Phytomedicine; Therapeutic Properties; curcumin; turmeric